Digital Piracy among Young Adults: The Role of Values and Time Perspectives - Bayraktar, Fatih; Tomczyk, Lukasz (Mdpi, 2021)
The aim of the research is to measure the extent of piracy among young adults and to relate this phenomenon to variables, such as values and time orientation. The research fits into the risk paradigm of cyber research. The research was carried out in Northern Cyprus, a country with a persistently high rate of digital piracy. The research involved 318 young adults (Mean Age: 20.9, SD: 2.47). The research process was conducted through the triangulation of three questionnaires: Piracy Risk Scale, Time Perspective Inventory, and the Values Scale. Based on the data collected, it was noted that piracy is not a rare phenomenon among young people (similar to other e-risks), and it is most common for files related to entertainment to be systematically downloaded. Digital piracy is linked to the level of digital competence, as well as hedonistic and fatalistic attitudes to time and values such as materialism and sense of honour. Despite technological developments maximising the legal circulation of cultural and other digital content, piracy has still not been completely eliminated.
Keywords: digital piracy; North Cyprus; young adults; time perspectives; values